2014
DOI: 10.2478/s13536-013-0172-y
|View full text |Cite
|
Sign up to set email alerts
|

A new route of emulsifier-free emulsion polymerization for the preparation of polymer coated magnetite nanoparticles

Abstract: A new route of emulsifier-free emulsion polymerization based on the homogenous mechanism was investigated to prepare magnetic nanoparticles coated by poly (methyl methacrylate) (PMMA). The experimental results confirm the formation of PMMA thin and unique layers covering magnetite cores. The polymer layer thickness, determined from transmission electron microscopy (TEM) images, increases from 4.3 nm to 6.8 nm with increasing mass ratio of MMA to magnetite from 3:1 to 11:1. The increase of the polymer thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The sample has a characteristic absorption band of the Fe–O bond of Fe 3 O 4 at 568 cm –1 . , The signal appeared at around 1130 cm –1 , which corresponds to the alkylsulfonium group. The bands at ∼1643 cm –1 correspond to iron oxide and the alkylsulfonium group too, while the band at 1736 cm –1 corresponds to the remaining H 2 SO 4 . , The O–H stretching bands from physisorbed molecular water can be observed at 3386 cm –1 , while the signals at 2957 and 2854 cm –1 belong to the C–H stretching signal of the inhibitor aliphatic group and Fe 3 O 4 . , The C–H scissoring of the alkyl chain signals appears at 1459 cm –1 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The sample has a characteristic absorption band of the Fe–O bond of Fe 3 O 4 at 568 cm –1 . , The signal appeared at around 1130 cm –1 , which corresponds to the alkylsulfonium group. The bands at ∼1643 cm –1 correspond to iron oxide and the alkylsulfonium group too, while the band at 1736 cm –1 corresponds to the remaining H 2 SO 4 . , The O–H stretching bands from physisorbed molecular water can be observed at 3386 cm –1 , while the signals at 2957 and 2854 cm –1 belong to the C–H stretching signal of the inhibitor aliphatic group and Fe 3 O 4 . , The C–H scissoring of the alkyl chain signals appears at 1459 cm –1 .…”
Section: Resultsmentioning
confidence: 98%
“… 71 , 72 The O–H stretching bands from physisorbed molecular water can be observed at 3386 cm –1 , while the signals at 2957 and 2854 cm –1 belong to the C–H stretching signal of the inhibitor aliphatic group and Fe 3 O 4 . 73 , 74 The C–H scissoring of the alkyl chain signals appears at 1459 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Literature findings showed that FTIR spectra of magnetite, which exhibits two strong infrared absorption bands at 570 cm −1 (υ1) and 390 cm −1 (υ2), can be assigned to the Fe-O stretching mode of the tetrahedral and octahedral sites for the υ1 band and the Fe-O stretching mode of the octahedral sites for the υ2 band 22 . These main Fe-O vibration bands may differ as function of various factors related to magnetite synthesis protocol, oxidation, stoichiometry of magnetite (Fe(II)/Fe(III) ratios), etc [23][24][25][26][27][28][29][30][31] . As an example, FTIR investigation of hydrothermally synthetized magnetite showed the two absorption bands at 584 cm −1 and 442.03 cm −1 respectively 32 .…”
Section: Resultsmentioning
confidence: 99%
“…For characterizing the samples, TGA data were used for estimating both polymer contents and polymer‐shell thickness. Then, the results were correlated with magnetization . Another interesting work was reported by Chen and co‐workers .…”
Section: Combination Of Thermal Gravimetric Analysis and Magnetizationmentioning
confidence: 85%